Effects of Rolapitant Administered Intravenously on the Pharmacokinetics of a Modified Cooperstown Cocktail (Midazolam, Omeprazole, Warfarin, Caffeine, and Dextromethorphan) in Healthy Subjects. (25th April 2018) - Wang, Xiaodong; Zhang, Zhi‐Yi; Arora, Sujata; Wang, Jing; Lu, Sharon; Powers, Dan; Kansra, Vikram
Abstract: Rolapitant is a selective, long‐acting neurokinin‐1 receptor antagonist, approved in the United States and Europe for prevention of delayed chemotherapy‐induced nausea and vomiting in adults. This open‐label study evaluated the effects of a new intravenous formulation of rolapitant on cytochrome P450 (CYP) enzyme (CYP3A, CYP1A2, CYP2C9, CYP2C19, and CYP2D6) activity. On days 1 and 14, 36 healthy volunteers received a modified Cooperstown cocktail (midazolam 3 mg [CYP3A substrate], caffeine 200 mg [CYP1A2 substrate], S‐warfarin 10 mg [CYP2C9 substrate] + vitamin K 10 mg, omeprazole 40 mg [CYP2C19 substrate], and dextromethorphan 30 mg [CYP2D6 substrate]). On day 7, subjects received the modified Cooperstown cocktail after 166.5‐mg rolapitant infusion. On days 21, 28, and 35, subjects received oral dextromethorphan. Maximum plasma concentration (Cmax ) and area under the plasma concentration‐time curve (AUC0‐last ) of probe drugs post‐ vs pre–rolapitant administration were assessed using geometric least‐squares mean ratios (GMRs) with 90%CIs. The 90%CIs of the GMRs were within the 0.80–1.25 no‐effect limits for caffeine and S‐warfarin Cmax and AUC0‐last . For midazolam Cmax and AUC0‐last and omeprazole Cmax, the 90%CIs of the GMRs were marginally outside these limits. Intravenous rolapitant coadministration increased dextromethorphan exposure, peaking 14 days post–rolapitant administration (GMRs: Cmax, 2.74, 90%CI 2.21–3.40; AUC0‐last, 3.36, 90%CI 2.74–4.13). Intravenous rolapitant 166.5 mg and probe drugs were well tolerated when coadministered. These data suggest that intravenous rolapitant is not an inhibitor of CYP3A, CYP2C9, CYP2C19, or CYP1A2 but is a moderate inhibitor of CYP2D6.